Minat Belajar Peserta Didik Kelas XI KI 4 SMK SMTI Makassar pada Materi Reaksi Redoks - Wanti, Fitrah; Danial, Muhammad; Hasri, Hasri (Program Pasca Sarjana UNM, 2024)
This research is a quasi-experimental research which aims to determine the learning interest of grade XI KI 4 students at SMK SMTI Makassar towards the main material of redox reactions. The research design uses the matching pretest-posttest design. The population in this study was all students in grade XI majoring in Industrial Chemistry (KI) at SMK SMTI Makassar with the total of 98 students were divided into four classes, and the research sampels were the students of grade XI KI 4. The results of the descriptive analysis of learning interest obtained an average of 81. The results of the inferential analysis of learning interest by using the t test obtain a significant value of 0.00<0.05 which indicated that there are an increase in learning interest of class XI KI 4 students. Therefore, the conclusion of the research is that there is an increase in students' interest in learning class XI KI 4 SMK SMTI Makassar on redox reactions subject.